Sensorial, nutritional and microbiological quality bread enriched eggshell (Research, Society and Development, 2021)
This study aims to prepare a homemade bread added with eggshell flour and evaluate its sensory, nutritional, and microbiological quality. Three bread formulations were prepared to contain potato, soy oil, eggs, crystal sugar, green coconut milk, eggshell flour, dry biological yeast, nutmeg and salt, and different proportions of traditional and whole wheat flour. The project was approved by the Ethics and Research Committee of Centro Universitário Una de Belo Horizonte. The acceptability test was carried out using the hedonic scale and the purchase and consumption intention tests. The bromatological analysis of protein, fat, fiber, calcium, sodium, moisture and ash for the preparation of nutritional information containing energy value, carbohydrates, proteins, total fats, saturated fats, trans fats, dietary fiber, calcium, and sodium were carried out in the sample. better acceptability. Microbiological analyzes of coagulase-positive Staphylococci, presumptive Bacillus cereus, yeasts and molds, Escherichia coli, and Salmonella spp. The global evaluation of the formulations F1, F2, and F3 for the sensory attributes had averages of 7.87±1.09; 8.06±1.28, and 7.74±1.54 and for the intention to consume and purchase 5.6±1.30; 5.74±1.67 and 5.48±1.73, respectively. The bread was presented as a food source of fiber, low in sodium, and within the microbiological standards for consumption. It was concluded that the homemade bread added with lactose-free eggshell flour obtained great acceptance among the evaluators and proved to be a product with great market potential.